Vimentin promotes actin assembly by stabilizing ATP-actin subunits at the barbed end - Lilian Paty; Lukas Kalvoda; Maritzaida Varela-Salgado; Quang D. Tran; Martin Lenz; Antoine Jegou; Guillaume Romet-Lemonne; Cécile Leduc (Proceedings of the National Academy of Sciences, 2026)
Vimentin intermediate filaments play essential roles in maintaining cell integrity and regulating numerous cellular functions. In particular, vimentin cooperates with the actin cytoskeleton in key cellular processes that rely on actin dynamics, such as migration, division, and mechanosensing. While there is evidence that these two cytoskeletal components interact in cells, the underlying molecular mechanisms are only partially understood. Actin and vimentin can interact through biochemical signaling pathways or via cross-linkers, but whether they engage in a direct protein–protein interaction has remained controversial, in part because such interactions are difficult to isolate and characterize in cells. Using in vitro reconstitution coupled to theoretical modeling, and total internal reflection fluorescence microscopy to monitor the elongation of single actin filaments, we show that vimentin promotes actin elongation by stabilizing actin subunits at the barbed end in a dose-dependent manner. Strikingly, this effect depends on the nucleotide state of actin, as the acceleration is only observed for the elongation from adenosine triphosphate (ATP)-actin, and not adenosine diphosphate (ADP)-actin monomers. We further establish that neither the vimentin tail nor head domains are required for this effect, and both filamentous and nonfilamentous vimentin enhance actin elongation. Finally, we find that vimentin promotes the nucleation of actin filaments. Consistently, magnetic pull-down assays demonstrate a direct interaction between vimentin and ATP-actin monomers. Altogether, these findings identify vimentin as an unexpected new actor in the regulation of actin dynamics at the barbed end and bring new insights into the functional role of vimentin through cytoskeletal crosstalk.